2014
DOI: 10.2147/opth.s61871
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ranibizumab injections on fluorescein angiographic findings and visual acuity recovery in age-related macular degeneration

Abstract: AimThe objective of the study reported here was to evaluate the effect of ranibizumab on retinal circulation times and vessel caliber and to analyze the correlation of these factors with visual acuity (VA) prognosis in patients with age-related macular degeneration (AMD).Subjects and methodsThis prospective cohort study included 52 eyes of 46 patients (mean age 73.5 years [standard deviation 7.7]; 28 males, 18 females). The study parameters were best-corrected visual acuity (BCVA), central macular thickness (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…A great improvement in BCVA was found, along with a signi cantly decreased CMT measured by OCT and aqueous humor contents of VEGF-A, VEGF-D, and endoglin, but signi cantly decreased content of EGF after consecutive intravitreal injections of ranibizumab. The results were similar to those from another study on the effects of ranibizumab in AMD cases [25]. The concentrations of cytokines may be quantitative indicators of the effects of ranibizumab in patients with myopic CNV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A great improvement in BCVA was found, along with a signi cantly decreased CMT measured by OCT and aqueous humor contents of VEGF-A, VEGF-D, and endoglin, but signi cantly decreased content of EGF after consecutive intravitreal injections of ranibizumab. The results were similar to those from another study on the effects of ranibizumab in AMD cases [25]. The concentrations of cytokines may be quantitative indicators of the effects of ranibizumab in patients with myopic CNV.…”
Section: Discussionsupporting
confidence: 87%
“…Ranibizumab (Lucentis; Novartis Pharma AG, Switzerland) is speci cally adopted to stop the active forms of VEGF-A [8] as a humanized, recombinant, monoclonal antibody fragment. Intravitreal injections of ranibizumab have demonstrated a curative effect on visual acuity improvement among patients with myopic CNV [9][10]. Further investigation is required to elucidate the clinical effects and mechanism of action of ranibizumab in the treatment of myopic CNV.…”
Section: Introductionmentioning
confidence: 99%
“…The authors compiled the VA gains reported by the individual RBZ studies to identify if there were significant differences/imbalances in the mean VA gain and in the clinical practice in RBZ studies completed both before and after 2015. The analysis of the individual data shows that the earlier studies (prior to 2015) report some of the highest and more consistent gains in visual acuity among the RBZ studies (Rothenbuehler et al [36], Gillies et al [41], Finger et al [43], Gungel et al [44], Inoue et al [45]). (See Appendix 1D in the supplementary material.)…”
Section: Discussionmentioning
confidence: 81%
“…1). After review, 24 observations from 23 studies were selected for inclusion in the meta-analysis (7 observations for intravitreally administered aflibercept [12-16, 34, 35] and 17 for RBZ [34,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]) (Appendix 1 in the supplementary material). One study contributed more than one observation because it reported several subgroups, including both intravitreally administered aflibercept and RBZ [34].…”
Section: Meta-analysismentioning
confidence: 99%